The Panegyric Rhetoric in the First Histories of the Conquest of Mexico - Marialba Pastor (Iberoamericana. América Latina - España - Portugal, 2020)
This text highlights the characteristics of the panegyric rhetoric and its use in the writing of the civil and religious chronicles of the conquest of Mexico in the sixteenth century, in order to illuminate some of its repercussions in the historical evaluation of the facts lived and in the interpretations of the indigenous past.